Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Minat Beli Produk Skincare Scarlett Whitening Pada Official Store Scarlett Whitening Di Shopee - Defi Setyawati; Farah Oktafani (STIE Mandala Jember, 2023)
This study aims to determine the effect of Product Quality, Service Quality and Price on Interest in Buying Scarlett Whitening Skincare at the Scarlett Whitening Official Store at Shopee simultaneously and partially. Collecting data in this study through the distribution of questionnaires and using descriptive quantitative data analysis. Sampling was done by non-probability sampling method, namely by purposive sampling technique. The sample used in this study were consumers who had visited the Scarlett Whitening official store at Shopee, with a total of 100 respondents. The method of analysis in this study is multiple regression analysis test. Based on the results of the F test in this study, it shows that the variables of product quality, service quality and price have a simultaneous effect on buying interest skincare Whitening official store at Shopee by 79%. Furthermore, based on the t-test that product quality partially affects buying interest with a percentage of 33.9%, service quality partially affects buying interest with a percentage of 23% and price partially affects buying interest with a percentage of 22.1%.